1993
DOI: 10.1111/j.1525-1594.1993.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Formation of Multicellular Spheroids of Adult Rat Hepatocytes by Rotation Culture and Their Immobilization within Calcium Alginate

Abstract: Tyrosine aminotransferase (TAT) induction and albumin secretion abilities were examined in rat hepatocytes immobilized within calcium alginate; the immobilized hepatocytes lost these abilities within a week. An attempt was then made to immobilize multicellular spheroids of hepatocytes for the purpose of stabilizing the liver functions. Although it takes at least 4 days to form spheroids in the conventional method using monolayer‐cultured cells, in this study we developed a new method for rapid spheroid formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The material chosen here, sodium alginate, is widely used for cells encapsulation both in vitro [2931] and in vivo [32,33]. Even though unmodified alginate-based hydrogel does not support interaction with cells directly [34] it is possible to use them as a scaffold for cell immobilization that can lead to aggregation [35]. However, if needed, alginate can be modified with specific cell attachment proteins or blended with different biomaterials such as silk fibroin to improve cell adhesion [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The material chosen here, sodium alginate, is widely used for cells encapsulation both in vitro [2931] and in vivo [32,33]. Even though unmodified alginate-based hydrogel does not support interaction with cells directly [34] it is possible to use them as a scaffold for cell immobilization that can lead to aggregation [35]. However, if needed, alginate can be modified with specific cell attachment proteins or blended with different biomaterials such as silk fibroin to improve cell adhesion [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Also, alginate polymer is stable in culture for weeks yet can be easily depolymerized to release the cells within simply by lowering the calcium concentration. [26][27][28][29] In the past, alginate encapsulation has been used for cultures of hepatocytes and for cell lines. 30,31 Recently Chandrasekaran et al 18 showed that mouse hepatic progenitor cells cultured in alginate produce viable, long-term cultures.…”
Section: Discussionmentioning
confidence: 99%
“…8), all three extracellular matrix components investigated, namely collagen type I, collagen type II, and aggrecan were identified in the beads qualitatively. Given the hydrophilicity of alginate and consequent lack of cell adhesion to the material,53–55 cells commonly form aggregates when encapsulated in alginate,55, 58 and the presence of the extracellular matrix components was generally observed qualitatively in the micrographs surrounding clusters of cells (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%